THE ROLE OF WOMEN IN THE QUR’AN: AN EXEGETICAL STUDY OF SURAH AN-NISĀ’/4:32 - Otong Surasman (Takafu: Journal of Tafsir and Gender Perspective, 2026)
This article examines the role of women from the perspective of the Qur'an through an interpretive study of Surah An-Nisā' verse 32. The study proceeds from the observation that Qur'anic verses on gender relations are often read partially, producing reductive conclusions about women’s position. This research employs a qualitative approach with library research as its principal method, bringing classical exegesis, contemporary tafsir, and relevant recent journal scholarship into dialogue. The findings demonstrate that Surah An-Nisā' verse 32 does not place women in a subordinate position; rather, it affirms respect for women’s effort, responsibility, and moral-social contribution. The verse provides a normative basis for recognising women’s roles in family, education, economic life, and wider socio-religious participation. Accordingly, the verse is more accurately understood as a foundation for proportional justice than as a justification for restricting women’s roles.